Analisis Saluran Drainase Pengendali Limpasan Permukaan Ruas Jalan Dusun Telaga Piru Kabupaten Seram Bagian Barat - Tuhelelu, Juraidah Lili Yanti; Hamkah, Hamkah; Kakaly, Sulastri (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
In the drainage channel analysis of the Telaga-Piru Hamlet section in West Seram District, West Seram Regency, Maluku Province. The research location road is 3 km long and 4 m wide. This surface runoff is caused by high intensity rain, so that the Telaga Piru road has a damaged surface, some of which is even covered by sediment and water that is carried onto the road. From the results of the 10 year return period calculation, the design rainfall was 192.518 mm, with an average water requirement of 125 liters and a water usage time of 24 hours/day from the water requirement discharged each day, namely 85% with population plant presentations of 0,21% peryear. So that the population of telaga hamlet in 2029 was 659 people/person.Then the discharge that enters the channel is 0,006 m³/hour/day. So the results of the analysis of the amount of runoff entering the Telaga Hamlet road section, Qᵣ = 0.522 m³/second and Qₛ = 0.527 m³/second, show that the channel on the Telaga Hamlet road section can accommodate the runoff discharge.